Pengaruh pemberian aroma therapy lavender Terhadap tingkat kecemasan ibu hamil trimester III menghadapi persalinan - Rudi Karmi; Ryka Juaeriah; Santi Susanti (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: In 2019, the World Health Organization (WHO) revealed that approximately 12.230.142 pregnant women worldwide experienced problems during the third trimester of pregnancy, with 30% experiencing anxiety during childbirth. The incidence of anxiety among pregnant women in Indonesia reached 28.7%, particularly among third-trimester pregnant women who were about to give birth. Pregnant women experiencing anxiety require efforts to reduce it. Pregnant women with anxiety increase the incidence of preeclampsia by up to 7.84 times, so if not addressed promptly, it will impact the well-being of both the mother and the baby. Purpose: The objective of this study is to determine the effect of lavender aromatherapy on anxiety levels in third-trimester pregnant women facing childbirth. Method: This is a quantitative study using a pre-experimental design with a one-group pretest-posttest. Respondents completed a questionnaire about anxiety before and after the lavender aromatherapy intervention. There was no control group in this study. Results: Among the 11 respondents before receiving lavender aromatherapy, 2 experienced severe anxiety, 6 experienced moderate anxiety, 1 experienced mild anxiety, and 2 were not anxious. After the first lavender aromatherapy intervention, the results showed 1 person with severe anxiety, 5 with moderate anxiety, 3 with mild anxiety, and 2 without anxiety. Subsequently, the respondents received the second lavender aromatherapy intervention, resulting in 1 person with moderate anxiety, 2 with mild anxiety, and 8 without anxiety. After the third application of lavender aromatherapy, the results showed that 2 individuals experienced moderate anxiety and 9 individuals did not experience anxiety. Conclusion: Using the Wilcoxon test after three interventions with lavender aromatherapy on 11 pregnant women, the results showed a p-value of 0.003 < 0.05, indicating that lavender aromatherapy has an effect on the anxiety levels of pregnant women facing childbirth.